Hubungan Tingkat Pengetahuan Tentang Perawatan Kritis dengan Tingkat Stress Kerja Perawat di Ruang Intensive Care Unit (ICU) Rumah Sakit Umum: The Relationship Between Knowledge Levels About Critical Care and the Level of Work Stress of Nurses in the Intensive Care Unit (ICU) of a General Hospital - Limbong, Tetty Suriany (Chakra Brahmanda Lentera Institute, 2025)
Nurses working in the Intensive Care Unit (ICU) face high work pressure, which can lead to stress. Knowledge of critical care is thought to play a crucial role in helping nurses manage this work pressure. Objective: This study aimed to determine the relationship between knowledge levels about critical care and work stress levels among nurses in the ICU at Bina Kasih General Hospital, Medan. This study used a quantitative approach with a cross-sectional design. A sample of 45 nurses was drawn using a purposive sampling technique. The instruments used were a knowledge level questionnaire and a modified work stress questionnaire. Data analysis was performed using the Spearman Rank test using SPSS version 25. The study showed that the majority of nurses had high knowledge (46.7%) and moderate levels of work stress (44.4%). There was a significant relationship between knowledge levels and work stress levels (p = 0.003) with a moderate negative correlation (r = –0.542), meaning that the higher the nurse's knowledge, the lower their work stress levels. Nurses' knowledge of critical care plays a significant role in reducing work stress levels in the ICU. Regular training and competency building are needed as strategies to prevent work stress. Further research is expected to explore other variables that influence nurses' work stress.